Multicenter Study of 342 Anorectal Malformation Patients: Age, Gender, Krickenbeck Subtypes, and Associated Anomalies - Banu, Tahmina; Karim, Anwarul; Adel, Maryam Ghavami; Lakhoo, Kokila; Aziz, Tasmiah Tahera; Das, Arni; Sharmeen, Nugayer; Yapo, Benjamin; Ferdous, Kazi Md Noor-ul; Kabir, Kh Ahasanul; Zahid, Mirza Kamrul; Ford, Kathryn; Ahsan, Md Qumrul; Akter, Mastura; Alam, Md Afruzul; Hoque, Mozammel (European Journal of Pediatric Surgery, 2019)
Introduction Published studies based on Krickenbeck classification of anorectal malformations (ARMs) are still insufficient to assess the global as well as regional relative incidence of different ARM subtypes, gender distribution, and associated anomalies. The primary purpose of this study was to provide an estimate of those in Global Initiative for Children's Surgery (GICS) research group.Materials and Methods We collected ARM data prospectively for 1 year from four institutes of different geographic locations. A total of 342 patients were included in this study (195, 126, 11, and 10 from Bangladesh, Iran, Papua New Guinea, and Oxford, United Kingdom, respectively).Results Overall male to female ratio was 1:1. The most frequent ARM subtype was perineal fistula (23.7% = 81/342). About 48.5% (166/342) patients had at least one associated anomaly. Cardiac and genitourinary systems were the most commonly affected systems, 31.6% (108/342) and 18.4% (63/342), respectively. These organ-systems were followed by anomalies of vertebral/spinal (9.9% = 34/342), musculoskeletal (4.4% = 15/342), and gastrointestinal/abdominal (3.2% = 11/342) systems. Rectovesical fistula had the highest percentage (96.4% = 27/28) of associated anomalies. About 18.1% (62/342) patients had multiple anomalies. ARMs (both isolated and with associated anomalies) occurred equally in males and females. Comparison between patients from Bangladesh and Iran showed differences in relative incidence in ARM subtypes. In addition, Iranian patient group had higher percentage of associated anomalies compared with Bangladeshi (73 vs. 35.4%).Conclusion Our study provides important insights about ARM subtypes, gender distribution and associated anomalies based on Krickenbeck classification especially from Bangladesh and Iran.
Keywords: Global Initiative for Children’s Surgery; congenital anomalies; anorectal malformations; VACTERL